EFFECT OF SELF-INSTRUCTION ON ATTITUDE TO LYING AMONG SECONDARY SCHOOL STUDENTS IN ANAMBRA STATE (Journal of Guidance and Counselling Studies, 2020)
This study is on the effect of self-instruction on attitude to lying among secondary school students in Anambra state. One research question and one null hypothesis guided the study. Pre test, post test control quasi-experimental design was adopted. The population was 286 students who were identified by counsellors and class teachers to have positive attitude to lying in the 18 secondary schools in Awka South local Government Area in Anambra state. Two co-education secondary schools that had the highest number of liars were selected for the study. Purposive Sampling was used to select 64 students who scored above the norm of 75 in the instrument. Thirty-item researcher developed questionnaire, Lying Attitude Inventory structured on a five-point scale ranging from 'Strongly Agree' to ' Strongly Disagree was used for data collection. Mean and ANCOVA were used to answer the research question and test the hypothesis. Finding showed that self-instruction significantly reduced positive attitude to lying among students. Therefore, it was recommended that counsellors, teachers and significant others in secondary schools should adopt self-instruction technique in controlling attitude to lying among students.
Keywords: Self-instruction; Attitude to lying; Secondary school; Students